Artemisinin-treatment in pre-symptomatic APP-PS1 mice increases gephyrin phosphorylation at Ser270: a modification regulating postsynaptic GABAAR density - Kiss, Eva; Kins, Stefan; Gorgas, Karin; Orlik, Maret; Fischer, Carolin; Endres, Kristina; Schlicksupp, Andrea; Kirsch, Joachim; Kuhse, Jochen (Biological chemistry, 2022)
Artemisinins, a group of plant-derived sesquiterpene lactones, are efficient antimalarial agents. They also share anti-inflammatory and anti-viral activities and were considered for treatment of neurodegenerative disorders like Alzheimer’s disease (AD). Additionally, artemisinins bind to gephyrin, the multifunctional scaffold of GABAergic synapses, and modulate inhibitory neurotransmission in vitro . We previously reported an increased expression of gephyrin and GABA A receptors in early pre-symptomatic stages of an AD mouse model (APP-PS1) and in parallel enhanced CDK5-dependent phosphorylation of gephyrin at S270. Here, we studied the effects of artemisinin on gephyrin in the brain of young APP-PS1 mice. We detected an additional increase of gephyrin protein level, elevated gephyrin phosphorylation at Ser270, and an increased amount of GABA A R-γ2 subunits after artemisinin-treatment. Interestingly, the CDK5 activator p35 was also upregulated. Moreover, we demonstrate decreased density of postsynaptic gephyrin and GABA A R-γ2 immunoreactivities in cultured hippocampal neurons expressing gephyrin with alanine mutations at two CDK5 phosphorylation sites. In addition, the activity-dependent modulation of synaptic protein density was abolished in neurons expressing gephyrin lacking one or both of these phosphorylation sites. Thus, our results reveal that artemisinin modulates expression as well as phosphorylation of gephyrin at sites that might have important impact on GABAergic synapses in AD.
published online April 20, 2021
Gesehen am 17.01.2022